2019
DOI: 10.1038/s41598-018-37580-w
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of dental surface nanofilaments and remineralisation by SnF2 and CPP-ACP nanocomplexes

Abstract: Dental caries, erosion and hypersensitivity are major public health problems. SnF2 is used widely in oral care products to help prevent/treat these conditions. Casein phosphopeptide-stabilised amorphous calcium phosphate nanocomplexes (CPP-ACP) are a biomimetic nanotechnology of salivary phosphopeptide-ACP complexes that deliver bioavailable calcium and phosphate ions to promote dental remineralisation (repair). We show here using in vitro studies and a double-blind, randomised controlled, cross-over design in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 35 publications
1
18
0
3
Order By: Relevance
“…The adhesion of the CPP-ACPF complexes to the dentinal surface relies on the higher ability of the CPP-ACP compounds to dissolve in aqueous solutions, such a saliva, which generates a diffusion gradient [42], that combined to the adhesive nature of the CPP allows the CPP-ACPF nanocomplexes to locate over the supragingival plaque and the dentinal surface [37,43]. In this scenario, the negatively charged residues of the CPP are attracted to the exposed positively charged apatite crystals faces on the surface allowing the CPP adsorption and the release of the cargo of calcium, phosphate and fluoride ions contained within the cross-linked nanocomplexes [38,44,45]. The release of these ions onto the dentinal surface has a remineralizating effect through the precipitation as fluorapatite crystals forming a nanofilament coating, that occludes the open dentinal tubules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adhesion of the CPP-ACPF complexes to the dentinal surface relies on the higher ability of the CPP-ACP compounds to dissolve in aqueous solutions, such a saliva, which generates a diffusion gradient [42], that combined to the adhesive nature of the CPP allows the CPP-ACPF nanocomplexes to locate over the supragingival plaque and the dentinal surface [37,43]. In this scenario, the negatively charged residues of the CPP are attracted to the exposed positively charged apatite crystals faces on the surface allowing the CPP adsorption and the release of the cargo of calcium, phosphate and fluoride ions contained within the cross-linked nanocomplexes [38,44,45]. The release of these ions onto the dentinal surface has a remineralizating effect through the precipitation as fluorapatite crystals forming a nanofilament coating, that occludes the open dentinal tubules.…”
Section: Discussionmentioning
confidence: 99%
“…The release of these ions onto the dentinal surface has a remineralizating effect through the precipitation as fluorapatite crystals forming a nanofilament coating, that occludes the open dentinal tubules. [45,46]…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation showed significant heterogenicity in the surface hardness values, due to which a random model of analysis was performed which included 5 of the 8 studies selected and which showed values (SMD = 1.19, 95% CI: [0.72, 1.66], p < 0.00001) indicating that the use of CPP–ACP resulted in superior remineralisation. The atomic force microscopy (AFM) analysis of three of their studies also showed that CPP–ACP’s use resulted in reduced roughness of the enamel surface and showed their ability to repair and form a smooth surface [ 14 , 15 ]. In another study by Fernando et al which described the use of SnF2 along with ACP–CCP to induce tooth repair, their in-vitro studies showed the ability of SnF2 to interact with CPP–ACP complexes to form a nanofilament coating on the tooth surface, with superior remineralisation activity in comparison to either of these materials individually.…”
Section: Biomimetics In Restorative Dentistrymentioning
confidence: 99%
“…ACP has been stabilised by casein phosphopeptides (CPP) derived from milk protein. Together they form CPP-ACP complexes which are reported to be 4 nm in diameter and have anti-cariogenic effects [ 33 , 34 ]. This is due to the ability of the phosphorylated amino acid cluster sequence [–Ser(P)–Ser(P)–Ser(P)–Glu–Glu–] within CPP to bind and stabilise calcium phosphate in the amorphous state, in addition to binding to dental plaque and enamel [ 35 , 36 ].…”
Section: Remineralisation Treatment and Preventive Dentistrymentioning
confidence: 99%